A new approach for calculation of relaxation time and magnetic anisotropy of ferrofluids containing superparmagnetic nanoparticles - Ahmadi R.; Hosseini Madaah H.R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this work, a new approach is described for the calculation of the relaxation time and magnetic anisotropy energy of magnetic nanoparticles. Ferrofluids containing monodispersed magnetite nanoparticles were synthesized via hydrothermal method and then heated using the 10 kA/m external AC magnetic fields in three different frequencies: 10, 50 and 100 kHz. By measuring the temperature variations during the application of the magnetic field, the total magnetic time constant including both Brownian and Neel relaxation times can be calculated. By measuring the magnetic core size and hydrodynamic size of particles, the magnetic anisotropy can be calculated too. Synthesized ferrofluids were characterized via TEM, XRD, VSM and PCS techniques and the results were used for the mentioned calculations.